ІДЕНТИЧНІСТЬ МІСТА ЯК СОЦІОКУЛЬТУРНИЙ ФЕНОМЕН - Tormakhova, Anastasiia (Ukrainian Cultural Studies, 2023)
The city is the center of modern society. Each of them was formed under certain socio-cultural conditions. During its existence, it was transformed, acquired a different visual image. It reproduces the change in worldview narratives that prevailed in society and appears as the factor influencing the formation of the cultural identity of the citizens. A city is not only a physical space in which people live. It is a cell that has its own unique character. The uniqueness of the city is defined as identity, as it is formed under the influence of historical and cultural development, as a result of the existence of collective memory, etc. The specifics of the city’s cultural identity largely depends on cultural memory. The concept of "collective memory" is formed in connection with a certain interpretation of the events of the past. The recipients should be included in historical milestones not so much on a rational-logical level, but mostly on an emotional one. The perception of the city is connected with aesthetic pleasure, but at the same time it appears as a certain construct. As a result of the process of globalization, the formation of cities with a more unified character is taking place. But the leadership of many cities seeks to focus on shaping a unique ethos of the city, which will be achieved through cultural policy, design and architecture. As a rule, such urban centers have significant popularity, a certain reputation and attract people who want to live there or at least visit it. The city and its ethos influence the formation of the identity of its inhabitants. And the residents themselves can act as the driving force that will shape the city’s identity in the conditions of the spread of globalization influences. Each of the big cities demonstrates compliance with a certain leading value that gives it originality and uniqueness. On the way to the formation of the global identity of the city, the cooperation of representatives of various institutions and citizens is extremely important, which is an example of interaction based on communication.